Karakteristik Sensori Produk Kopi 2 In 1 Komersial Menggunakan Metode Check-All-That-Apply (CATA) - Kurniawan, Muhammad Fakih; Lola, Amelia; Hapsari, Distya Riski (JURNAL AGROINDUSTRI HALAL, 2024)
The coffee industry in sachets is booming. Understanding the characteristics of product and what consumers want is the key to the success of the product developed. The purpose of this study was to obtain sensory profile information on commercial coffee 2 in 1 product using the CATA (Check-All-That-Apply) method. The testing method is divided into two, namely determining the sensory attributes of coffee by trained panelists through FGD (Focus Group Discussion) and CATA testing by consumer panelists including determining ideal attributes, coffee sample attributes and level of liking. The sensory attributes of coffee 2 in 1 based on FGD results for CATA testing are sweet aroma, acid aroma, roasted aroma, coffee aroma, caramel aroma, sweet taste, acid taste, bitter taste, caramel taste, coffee taste, watery body, thickness body, brown color, sandy texture, aftertaste bitter, aftertaste acid, and aftertaste sweet. The ideal coffee 2 in 1 product according to panelists should have a brown color, coffee aroma, coffee taste, roasted aroma, and sweet taste attributes. Attributes that affect consumer preferences are sweet taste, watery body, aftertaste sweet, coffee aroma, and brown color. The attributes of acid taste, acid aroma, and aftertaste acid are attributes that must not have and need to be considered for their existence. Product 235 has the highest level of favorability, which is 78%, while product 539 has the smallest percentage of 33%. Coffee 2 in 1 with ideal attributes according to consumers can still be developed further.